QTL Mapping and Inheritance of Clubroot Resistance Genes Derived From Brassica rapa subsp. rapifera (ECD 02) Reveals Resistance Loci and Distorted Segregation Ratios in Two F2 Populations of Different Crosses - Fredua-Agyeman, Rudolph; Jiang, Junye; Hwang, Sheau-Fang; Strelkov, Stephen E. (Frontiers in Plant Science, 2020)
In this study, Brassica rapa subsp. rapifera (ECD 02) which exhibits broad-spectrum resistance to many Canadian Plasmodiophora brassicae isolates was crossed with two clubroot-susceptible B. rapa accessions to produce two F2 populations. The F2 plants were screened against P. brassicae pathotypes 3H, 5X, and 5G. The Chi-square goodness of fit test showed that the vast majority (≈75%) of the crosses that produced the F2 populations showed segregation ratios of 9R:7S, 7R:9S, 13R:3S, 3R:13S, 5R:11S, 11R:5S, and 1R:15S. These were modifications of the 15R:1S ratio expected for the inheritance of two dominant major clubroot resistance (CR) genes from ECD 02. The distorted segregation ratios suggest that the two resistance genes are on different chromosomes and that two genes interact in an epistatic manner to confer resistance. Genotyping was conducted with 144 PCR-based markers in the two F2 populations. Linkage and QTL analysis with the polymorphic markers identified two QTLs on chromosome A03 to be associated with resistance to P. brassicae pathotypes 5X and 5G in Popl#1 while only the second QTL on chromosome A03 was associated with resistance to pathotypes 5X and 5G in Popl#2. The QTLs clustered in genomic regions on the A03 chromosome of B. rapa where the CRa/CRbKato gene(s) are mapped. In addition, the Crr1 gene on the A08 chromosome of B. rapa was detected in the two F2 populations. Therefore, the phenotypic and molecular data confirm the existence of two CR genes in ECD 02. This is the first study that shows that major dominant genes in Brassica interact in a non-additive manner to confer resistance to different P. brassicae pathotypes. Key Message: This study provides knowledge on the inheritance and type of gene action for clubroot resistance derived from Brassica rapa subsp. rapifera (ECD 02). The results indicated that duplicate recessive and recessive suppression epistatic interactions, digenic additivity and complementary gene action between the CRa/CRbKato gene(s) on the A03 and the Crr1 gene on the A08 chromosome of B. rapa controlled clubroot resistance to P. brassicae pathotypes 3H, 5X and 5G.